Bangladesh - Poverty Assessment for Bangladesh : Creating Opportunities and Bridging the East-West Divide - World Bank (Washington, DC, 2012)
Bangladesh represents a success story among developing countries. Poverty incidence, which was as high as 57 percent at the beginning of the 1990s, had declined to 49 percent in 2000. This trend accelerated subsequently, reducing the poverty headcount rate to 40 percent in 2005. The primary contributing factor was robust and stable economic growth along with no worsening of inequality. Respectable GDP growth that started at the beginning of the 1990s continued into the new millennium and averaged above 5 percent annually between 2000 and 2005. Inequality, as measured by the Gini coefficient of consumption, remained stable between 2000 and 2005. Recent shocks to the Bangladeshi economy in the form of natural disasters and rising food prices have partially dampened the rapid progress in reducing poverty. The year 2007 saw two natural disasters, floods and a devastating cyclone within a few months of each other. Another significant shock has been the steep rise in food prices, including the main staple, rice, which has revealed the risk posed by global price volatility for a net food-importing country like Bangladesh. Estimates in this report suggest that the impact of the food price shock has likely negated some of the reduction in poverty brought about by economic growth between 2005 and 2008. Specific areas for policy focus which are elaborated in the report include measures to: (i) promote growth by sustaining increases in labor productivity and job creation in manufacturing and services; (ii) expand opportunities in lagging regions by improving connectivity with growth poles and investing in human capital; (iii) facilitate migration from poor areas given the poverty-reducing impact of remittances; (iv) stimulate women's participation in the labor force (v) sustain Bangladesh's past successes in reducing fertility; (vi) improve poor households access to and quality of education, health, and nutrition services; and (vii) strengthen the coordination, targeting, and coverage of safety net programs.